1996
DOI: 10.1126/science.272.5264.1023
|View full text |Cite
|
Sign up to set email alerts
|

Binding of GSK3β to the APC-β-Catenin Complex and Regulation of Complex Assembly

Abstract: The adenomatous polyposis coli gene (APC) is mutated in most colon cancers. The APC protein binds to the cellular adhesion molecule beta-catenin, which is a mammalian homolog of ARMADILLO, a component of the WINGLESS signaling pathway in Drosophila development. Here it is shown that when beta-catenin is present in excess, APC binds to another component of the WINGLESS pathway, glycogen synthase kinase 3beta (GSK3beta), a mammalian homolog of Drosophila ZESTE WHITE 3. APC was a good substrate for GSK3 beta in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
1,014
2
16

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,346 publications
(1,061 citation statements)
references
References 26 publications
20
1,014
2
16
Order By: Relevance
“…In patients linked to familial adenomatous polyposis, truncations of or mutations in the APC gene are believed to enhance the progression of colorectal or gastric tumours, presumably through stabilisation of b-catenin in the cytoplasm (Rubinfeld et al, 1996). In the present study, APC expression was demonstrated in normal ovaries and benign tumours, but was low or absent in malignant ovarian tumours.…”
Section: Discussionsupporting
confidence: 44%
“…In patients linked to familial adenomatous polyposis, truncations of or mutations in the APC gene are believed to enhance the progression of colorectal or gastric tumours, presumably through stabilisation of b-catenin in the cytoplasm (Rubinfeld et al, 1996). In the present study, APC expression was demonstrated in normal ovaries and benign tumours, but was low or absent in malignant ovarian tumours.…”
Section: Discussionsupporting
confidence: 44%
“…The latter complexes with glycogen synthase 3␤ (GSK-3␤) and thus controls degradation of ␤-catenin. Mutations of the APC gene or the ␤-catenin gene itself can thus result in the nuclear accumulation of ␤-catenin protein (42,43). Because ␤-catenin is a component of the wnt-signaling pathway controlling cell proliferation, its unregulated accumulation leads ultimately to unchecked cell proliferation and neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The targeting of b-catenin for degradation involves the phosphorylation of its N-terminus by glycogen synthase kinase 3b (GSK) (Aberle et al, 1997;Yost et al, 1996) which occurs in a multi-protein complex consisting of b-catenin, GSK, the adenoma-tous polyposis coli (APC) tumor suppressor protein and axin/conductin Rubinfeld et al, 1996;Zeng et al, 1997;Ikeda et al, 1998;Behrens et al, 1998;Yamamoto et al, 1998). This complex associates with the ubiquitin ligase, b-TrCP (b-transducin repeat-containing protein) that recognizes the N-terminally phosphorylated forms of bcatenin and regulates its ubiquitination and degradation by the proteasome (Winston et al, 1999;Liu et al, 1999;Latres et al, 1999;Hart et al, 1999;Kitagawa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%